Producing High‐Strength Metals by I‐ECAP1 . Issue 2 (3rd September 2015) - Gzyl, Michal; Rosochowski, Andrzej; Boczkal, Sonia; Olejnik, Lech; Katimon, Mohd Nizam
Abstract : Incremental equal channel angular pressing (I‐ECAP) is used in this work to produce ultrafine‐grained (UFG) pure iron, aluminum alloy 5083, commercial purity titanium (grade 4), and magnesium alloy AZ31B. Pure iron is processed at room temperature, aluminum alloy at 200 °C, titanium at 320 °C, and magnesium alloy at 150 °C. Strength improvement, attributed to the grain refinement below 1 μm, is reported for all processed materials. The yield strength increase is the most apparent in pure iron, reaching almost 500 MPa after one pass of I‐ECAP, comparing to 180 MPa in the as‐forged conditions. UFG titanium, aluminum, and magnesium alloys obtained in this study reached yield stress of 800, 350, and 300 MPa, respectively, in each case exhibiting the yield strength increase by at least 30%, comparing to the alloys processed by conventional metal forming operations such as forging and rolling. Abstract : Incremental equal channel angular pressing (I‐ECAP) is used in this work to produce ultrafine‐grained: iron, titanium, aluminum, and magnesium alloys. The benefits include up to 50% strength increase, revealing weight‐saving opportunities for structural applications, and elimination of harmful or expensive alloying elements. The process has a great potential for implementation into industrial practice due to its incremental nature, which enables processing long billets.